Cardiomyocyte maturation and its reversal during cardiac regeneration - Beisaw, Arica; Wu, Chi-Chung (Developmental dynamics, 2024)
Cardiovascular disease is a leading cause of death worldwide. Due to the limited proliferative and regenerative capacity of adult cardiomyocytes, the lost myocardium is not replenished efficiently and is replaced by a fibrotic scar, which eventually leads to heart failure. Current therapies to cure or delay the progression of heart failure are limited; hence, there is a pressing need for regenerative approaches to support the failing heart. Cardiomyocytes undergo a series of transcriptional, structural, and metabolic changes after birth (collectively termed maturation), which is critical for their contractile function but limits the regenerative capacity of the heart. In regenerative organisms, cardiomyocytes revert from their terminally differentiated state into a less mature state (ie, dedifferentiation) to allow for proliferation and regeneration to occur. Importantly, stimulating adult cardiomyocyte dedifferentiation has been shown to promote morphological and functional improvement after myocardial infarction, further highlighting the importance of cardiomyocyte dedifferentiation in heart regeneration. Here, we review several hallmarks of cardiomyocyte maturation, and summarize how their reversal facilitates cardiomyocyte proliferation and heart regeneration. A detailed understanding of how cardiomyocyte dedifferentiation is regulated will provide insights into therapeutic options to promote cardiomyocyte de-maturation and proliferation, and ultimately heart regeneration in mammals.
Erstmals veröffentlicht: 11. Dezember 2022
Gesehen am 04.06.2024